Energy harvesting for charging system in wearable travel aid device for visually impaired person - Ayub, Nurul Nadia (2022)
Intelligent spectacle is one of electronic travel aid device that was used by visually impaired person to assist them in their daily life. It was used to detect obstacle in their path such as signboard, hanging pots and others that may cause injuries. This study aims to design a power charging system that can be used by visually impaired person easy and efficiently. The main objective is to evaluate the performances of power consumption, design energy harvesting circuit and analyzed power charging system on wearable device. It features experiment using solar, photodiode, thermoelectric generator and radio frequency in different configurations. The performance of power charging system was measured in terms of voltage,current and power. This research stated that the higher the intensity of light strike the surface of the harvester, the higher amount of energy produced. Radio frequency shows that the closer transmitter to receiver the higher energy can produced. The data was collected using the equipment of energy harvester and analyzed using graph analytics. The intelligent spectacle can be used up to 38 hours using a powerbank with a capacity of 2600mAH while a 130mAH Li-po battery can be used approximately 3 hours and 45 minutes. Solar produced the highest output energy at 4.33V, 0.34A and 1.47W while TEG produced the lowest output at 0.015V, 27mA and 0.4mW. This is due to its large in size of photovoltaic cell and higher efficiency in energy conversion. Series configuration shows maximum energy produced for photodiode at 1.47V, 3.47mA and 5.17mW. In order to give the comfortability and increase the quality of life for the visually impaired person, photodiode was chosen as it able to produce ample energy and it comes in smaller size. Thermoelectric generator was found as the least energy produced among other harvester. The validity was obstructed by a limited amount of light intensity during cloudy day and closeness of transmitter to receiver. In conclusion, photodiode was suitable to be used in wearable device as energy harvester but it needs to design with circuit booster.